Strategi Framing Visual dan Verbal dalam Konten Interaktif Instagram Pemerintah - Anisah Dwi Rahayu; Jusuf Fadilah; Eddy Kusnadi (Jurnal Riset Multidisiplin Edukasi, 2025)
Social media has become a strategic platform for government institutions to engage with the public in more effective and participatory ways. One increasingly utilized form of digital communication is interactive content such as Mini Quizzes, which combine visual and verbal elements to convey messages in an appealing manner. This study aims to systematically review how visual and verbal framing strategies are implemented in government communication content on social media, particularly Instagram. Employing a Systematic Literature Review (SLR) method, this study analyzes 10 scholarly articles published between 2020 and 2025 that focus on digital government communication, visual/verbal strategies, and framing theory. The review reveals that most studies emphasize heavy issues such as crises, public policy campaigns, and institutional image-building, while lighter and more engaging content like interactive quizzes remains underexplored. However, such content holds significant potential in shaping public perception through dialogic and participatory communication. By integrating Entman’s Framing Theory with the Uses and Gratifications approach, this study underscores the importance of balancing visual and verbal elements in constructing engaging narratives that enhance public trust and institutional visibility in digital environments.